Dementia care recommendations during the COVID-19 pandemic - Audronytė , E.; Sutnikienė , V.; Kaubrys , G. (Neurologijos seminarai, 2020)
The recommendations for dementia caregivers and health care professionals in long-term care facilities during the COVID-19 pandemic published by the Alzheimer’s Association, the European Academy of Neurology Dementia Scientific Panel, and Alzheimer Europe are presented in this review article. The main aspects of care and the emerging difficulties that should be taken into account when caring for dementia patients at home and in nursing homes in this rapidly changing emergency are highlighted.
Keywords: dementia; Alzheimer’s disease; COVID-19; pandemic